A one-step synthesis of hollow periodic mesoporous organosilica spheres with radially oriented mesochannels. Issue 17 (4th February 2016) - Ma, Ning; Deng, Yiqun; Liu, Wenting; Li, Shiji; Xu, Jie; Qu, Yanan; Gan, Ke; Sun, Xiaodan; Yang, Jinlong
Abstract : A new one-step method is proposed for the fabrication of nanosized hollow periodic mesoporous organosilica spheres with radially oriented mesochannels. Abstract : A simple and effective one-step method is proposed for the fabrication of hollow periodic mesoporous organosilica spheres (HPMOSs). The obtained HPMOSs possess well-defined spherical morphology, uniform and tunable particle size, adjustable hollow void structure, and radially oriented mesochannels in their shells.